Kajian Yuridis Penegakan Hukum terhadap Penambangan Ilegal di Kawasan IUP PT Antam Berdasarkan Perspektif Lingkungan Hidup - Khuszaimah Anggraheni Nur Amalia; Sulistyanta Sulistyanta (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
This study was conducted to implement the law on the case of illegal mining carried out by Chen Fu as a perpetrator of a criminal act in the Mining Business Permit (IUP) area of ​​PT ANTAM Tbk UBPN North Konawe, and to assess whether its implementation has accommodated ecological justice based on Law Number 3 of 2020 concerning Mineral and Coal Mining (Minerba Law) and Law Number 32 of 2009 concerning Environmental Protection and Management (PPLH Law). The method used in this is normative-doctrinal with a statutory approach and a case approach. Thus, the results of the study show that the legal approach in this case is still limited to the administrative aspect and does not substantially reflect ecological justice. There is a need for harmony between the Minerba Law and the PPLH Law in their implementation to reach aspects of ecological losses, strengthen the deterrent effect, and pave the way for comprehensive environmental recovery. The resulting research recommendations explain the importance of reforming charges in illegal mining cases that cause environmental damage, so that the law can be enforced fairly, comprehensively, and with a sustainable perspective.